The Peopling of America: craniofacial shape variation on a continental scale and its interpretation from an interdisciplinary view - González José, Rolando (2008)
Twenty-two years ago, Greenberg, Turner and Zegura (Curr. Anthropol. 27,477-495, 1986) suggested a multidisciplinary model for the human settlement of the New World.  Since their synthesis, several studies based mainly on partial evidence such as skull morphology and molecular genetics have presented competing, apparently mutually exclusive, settlement hypotheses.  These contradictory views are represented by the genetic-based “Single Wave” or “Out of Beringia” model and the cranial morphology-based “Two Components/Stocks” model.  Here, we present a geometric morphometric analysis of 576 late Pleistocene/early Holocene and modern skulls suggesting that the classical “Paleoamerican” and “Mongoloid” craniofacial patterns should be viewed as extremes of a continuous morphological variation.  Our results also suggest that recent contact among Asian and American circumarctic populations took place during the Holocene.  These results along with data from other fields are synthesized in a model for the settlement of the New World that considers, in an integrative and parsimonious way, evidence coming from genetics and physical anthropology.  This model takes into account a founder population occupying Beringia during the last glaciation characterized by high craniofacial diversity, founder mtDNA and Y-chromosome lineages, and some private autosomal alleles.  After a Beringian population expansion, which could have occurred concomitant with their entry into America, more recent circumarctic gene flow would have enabled the dispersion of northeast Asian-derived characters and some particular genetic lineages from East Asia to America and vice versa.